3DICE coding matrix multidirectional macro-architecture modulates cell organization, shape, and co-cultures endothelization network. (October 2021) - Canadas, Raphaël F.; Costa, João B.; Mao, Zhengwei; Gao, Changyou; Demirci, Utkan; Reis, Rui L.; Marques, Alexandra P.; Oliveira, Joaquim M.
Abstract: Natural extracellular matrix governs cells providing biomechanical and biofunctional outstanding properties, despite being porous and mostly made of soft materials. Among organs, specific tissues present specialized macro-architectures. For instance, hepatic lobules present radial organization, while vascular sinusoids are branched from vertical veins, providing specific biofunctional features. Therefore, it is imperative to mimic such structures while modeling tissues. So far, there is limited capability of coupling oriented macro-structures with interconnected micro-channels in programmable long-range vertical and radial sequential orientations. Herein, a three-directional ice crystal elongation (3DICE) system is presented to code geometries in cryogels. Using 3DICE, guided ice crystals growth templates vertical and radial pores through bulky cryogels. Translucent isotropic and anisotropic architectures of radial or vertical pores are fabricated with tunable mechanical response. Furthermore, 3D combinations of vertical and radial pore orientations are coded at the centimeter scale. Cell morphological response to macro-architectures is demonstrated. The formation of endothelial segments, CYP450 activity, and osteopontin expression, as liver fibrosis biomarkers, present direct response and specific cellular organization within radial, linear, and random architectures. These results unlock the potential of ice-templating demonstrating the relevance of macro-architectures to model tissues, and broad possibilities for drug testing, tissue engineering, and regenerative medicine.